Optimalisasi Media Digital Berbasis Kemaslahatan Umat dalam Program Pahlawan Ekonomi Surabaya - Rio Febriannur Rachman (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
This article discusses a number of challenges facing the city of Surabaya as one of the major cities in Indonesia. The city has a number of social problems, including poverty, economic disparity and welfare problems. All that has a correlation with each other, and one of the solutions, is the provision of employment. Since 2010, the City Government of Surabaya has been running the Pahlawan Ekonomi program, which makes Housewives the main target. With hope, they can become the “second economic engine” in the family. Pahlawan Ekonomi provides entrepreneurship training for Housewives, starting from the planning, production, packaging, to marketing. All stages are always under the supervision of a team from the City Government of Surabaya. This paper explores how the implementation of policy in this program, the sustainability, and its correlation to the concept of the Welfare of the People (Kemaslahatan Umat) which is called for in some number of Islamic literatures. In conclusion, this policy has many positive impacts on the community, so that its sustainability can be maintained because it is supported by many parties in Surabaya. The spirit of this program is in harmony with the noble Islamic principles. Moreover, this program has a tagline: Go Global, Go Digital, Go Financial, which makes the program participants ready to compete at the international level.